INTRODUCTION OF INTERACTIVE SCIENCE LEARNING IN COMMUNITY SERVICE AT KASIH ENDE ORPHANAGE - Paoki, Rouna; Leorina Evinita, Lenny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Education is a process to improve, to educate people's skills, attitudes, and behavior; and to govern a person or group in an effort to educate human life through teaching, training and guidance activities. Based on the situation in Ende district, there are social problems, one of which is the number of children dropping out of school due to several factors, such as the family condition. Through the Community Program , the community in Ende Orphanage was invited and involved in improving children's education. Based on the results, the community service found the children of the Naungan Kasih Orphanage participated in activities and gained knowledge based on the activities that had been carried out. The activity is how to increase knowledge with tutoring, such as waste classification and processing, clean and healthy lifestyle, character building, and education about the slogans and symbols of the Republic of Indonesia